The human capacity for transformational change : harnessing the collective mind - Brown, Valerie A.; Harris, John A. (London : Routledge, 2014)
'Pressures for transformational change have become a regular feature of most fields of human endeavour. This book presents the case that to succeed individually the power systems of society will need to work collectively. Inspired by the work of Teilhard de Chardin, Gregory Bateson and Heryk Skolwimoski and the results of the authors' research, this book offers ways and means of creating the synergies that are crucial in establishing a desired transformational change to a just and sustainable future'--
Includes bibliographical references (pages 214-224) and index.
Keywords: Sustainable development; Environmental policy; Environmental management; Human ecology; Social change; Power (Social sciences).